Perancangan Game Edukasi “Kabataku” Untuk Anak Sekolah Dasar Dengan Menggunakan Metode Quiz Team - Pranata S., Panca Wira; Nugroho, Agus; Roby Setiawan (LPPM Universitas Dinamika Bangsa, 2024)
This research is motivated by the absence of supporting applications for learning mathematics that can attract students' interest in learning mathematics at SD Negeri 130, Jambi City. This is because the learning and teaching system seems monotonous and boring by only using textbooks as the main teaching material. The purpose of this research is to design a kabataku educational game for elementary school children using the quiz team method. The system development method used is data collection and interviews and also uses the waterfall method using modeling tools use case diagrams, activity diagrams, class diagrams, and flowcharts. The software used is Contract 2, Pictart. By designing this educational game, you can add to the method of learning and teaching mathematics while playing the kabataku educational game using the quiz team method.